Design and Build Bali Tourism Information System in The Pandemic Time Based on Website (Future Science, 2021)
The island of Bali is one of the international tourist attractions that has long been known by tourists, especially from foreign countries. This must be supported by developing a tourist information system that can provide further information about tourist attractions and facilities on the island of Bali. One of the information system technologies that can support progress in the tourism sector is internet technology which has long been considered a technology that has succeeded in becoming an unlimited communication tool. The purpose of this study is to design and implement an information system that provides information, including suggestions and tourist attractions, including natural attractions, accommodation facilities, transportation facilities, places to sell art goods, restaurants, entertainment venues, and other facilities. For this reason, a database system and webserver application were designed along with an interface design that can be opened via an existing internet browser. In this study, for the manufacture of Web Server applications, the Back-end uses PHP. For the Front-end, the Javascript programming language is used. Meanwhile, for the creation of the database used SQL. It is hoped that the design and development of the Bali island tourism information system application can make it easier for domestic and foreign tourists to get information about the location and tourism facilities on the island of Bali quickly. Meanwhile, for the creation of the database used SQL. It is hoped that the design and development of the Bali island tourism information system application can make it easier for domestic and foreign tourists to get information about the location and tourism facilities on the island of Bali quickly.